NP-007 A mixed methods evaluation of the cross-sector pharmacist vocational training foundation programme: is the training programme fit for purpose?. (24th March 2020) - McMillan, FJ; Power, A; Bond, C; Clelland, J; Inch, J
Abstract : Background and importance: Pharmacists increasingly have portfolio careers, in different settings, including hospital, community and primary care. Aim and objectives: A cross-sector Pharmacist Foundation Training programme was introduced in Scotland from September 2017 1 to develop transferable skills and competences for pharmacists working in these sectors. The aim was to assess the effectiveness of the programme. Materials and methods: The approach was underpinned by two theoretical frameworks. 2 3 Pharmacists and tutors were invited to take part in focus groups at baseline, mid, and end-of-training, to explore their experiences. Proceedings were audio-recorded and transcribed. On-line baseline and end-of-training self-assessment questionnaires and routine assessment data were analysed. Data was managed in nVIVO v11 and analysed thematically Quantitative data from the questionnaires and assessments was analysed in SPSS and Excel. Results: Of the 72 registered FPs, 48 (67%) completed a baseline questionnaire. Twenty pharmacists (28%) and 16 tutors attended a focus group. Preliminary focus group themes include training/support needs, professional identity, patient safety, and training barriers/facilitators. Tutors highlighted skill gaps and noted variation in competence, training and support needs. Questionnaire analyses suggest that pharmacists feel part of the team. They are confident communicating with patients/carers, meeting their needs, and managing pharmaceutical care issues. but have less confidence dealing with supply chain issues or applying local formularies. Conclusions and relevance: Baseline data suggests pharmacists' high self-assessed competence is not matched by reflective focus group discussions or tutor feedback. Ongoing evaluation will confirm if the programme has enabled the development of the requisite competences for future practice. References and/or acknowledgements: 1. The Pharmacist Vocational Training programme. https://www.nes.scot.nhs.uk/education-and-training/by-discipline/pharmacy/pharmacists/pharmacy-vocational-training.aspxAccessed August 2018 2. Miller GE. The assessment of clinical skills/competence/performance. Academic Medicine 1990:65(9). September Supplement. 3. Lave J, Wenger E. Situated learning: legitimate peripheral participation . Cambridge: Cambridge University Press; 1991.